A New Approach Toward Resolving The Line and Staff Dilemma - Nossiter, Vivian (Academy of Management Review, 1979)
The article refers to management literature and the interdependency of line and staff members in an organization. Trends in management literature focus on the usefulness of the staff-and-line concept, the boundary-spanning aspect of the concept, and the change in attitude that is required to improve the line-staff relationship and make it more effective. The gap between theory and application has management costs such as additional noise in communication channels from unperceived differences in defining the functions and responsibilities of staff and line, as well as a dysfunctional increase in stress.